Fabrication and characterization of dye-sensitized solar cells incorporating polymer electrolyte liquid crystal system / Muhammad Akmal Kamarudin - Muhammad Akmal , Kamarudin (2013)
Gel polymer electrolytes are defined as solid ion conductors formed by dissolving salt in high molecular weight polymers using a balanced ratio in order to form a gel structure. They are typically found in applications such as fuel cells, lithium ion batteries and solar cells. In this research work, the potential of a gel polymer electrolyte doped with nematic liquid crystal, for solar cell applications are discussed. Polymer electrolytes have attracted a lot of attention due to ease of fabrication with low cost, minimum side reactions, long shelf-life, high ionic conductivity and excellent thermal stability. In this thesis, an approach to produce a high electrical conductivity gel polymer electrolyte thin film is presented. Here, a novel polymer electrolyte liquid crystal system consisting of polyvinyl alcohol (PVA), potassium iodide (KI) and 4-Cyano-4'-pentylbiphenyl (5CB) nematic liquid crystal (LC) has been fabricated. First the inclusion of the liquid crystal into the polymer electrolyte was confirmed by using the optical polarizing microscope where the phase transition temperature of the liquid crystal can also be determined. The ionic conductivity is characterized by using the impedance spectroscopy and four point probe method. The ionic conductivities of the sample prepared by two methods will be compared and the temperature dependence of the ionic conductivity will also be elucidated. The highest ionic conductivity achieved is 2.82 x 10-3 S/cm which is 66.9% higher than then one without the inclusion of liquid crystal. The thermal analysis of the sample will also be given using the differential scanning calorimetry. The phase transition temperature of the liquid crystal and the glass transition temperature of the polymer can be obtained from this characterization. Finally, the band gap of this material was obtained from cyclic voltammetry using a thin film of the mixture which was spin-coated onto ITO substrate. The curve obtained from the cyclic voltammetry (CV) test was used to determine the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO) and electrical band gap (Eg) of the material. The LC-doped polymer electrolyte showed a band gap of 1.557 eV whereas the LC-undoped polymer electrolyte showed a band gap of 1.657 eV. For a material to be used as a material in solar cell application, a band gap of 1.5 eV or less or less is required. Thus the narrowing of the band gap after the inclusion of liquid crystal shows the suitability of the material to be used as one of the components for solar cell.